Heat capacity of Rb2SO4(aq) and Cs2SO4(aq) solutions and thermodynamic modelling of (Rb2SO4 + H2O) and (Cs2SO4 + H2O) systems. (January 2020) - Fan, Yanfei; Li, Dongdong; Gao, Dandan; Zeng, Dewen; Li, Wu
Highlights: Determination of specific heat capacity of Rb2 SO4 (aq) and Cs2 SO4 (aq) solutions. Implementation of thermodynamic models for Rb2 SO4  + H2 O and Cs2 SO4  + H2 O systems. The models represent all the thermodynamic properties of the systems well. Abstract: Specific heat capacity of Rb2 SO4 (aq) and Cs2 SO4 (aq) solutions was determined using a Calvet-type calorimeter from 288.15 K to 338.15 K and from about 0.25 mol·kg −1 to concentration near room temperature solubility limits. For both Rb2 SO4 (aq) and Cs2 SO4 (aq) solutions, the specific heat capacity decreases with the increase of molality at constant temperature. Combining the heat capacity data determined in this study and other thermodynamic properties ( i.e. water activity, osmotic coefficient, mean ionic activity coefficient, enthalpy of dilution and solubility) reported in literature, thermodynamic and phase equilibria properties of the binary Rb2 SO4  + H2 O and Cs2 SO4  + H2 O systems were modelled using a comprehensive thermodynamic framework, in which a Pitzer-Simonson-Clegg model was applied to represent the non-ideality of aqueous phases. The models can represent all the properties over wide temperature and concentration ranges. This study forms a basis for solubility prediction in multi-component systems containing Rb and Cs sulfates.